Case Report of Foveolitis with Optic Neuritis: A Barely encountered Ophthalmic Manifestation of Dengue - Lama, Dichen M; Kharel Sitaula, Ranju (Journal of Institute of Medicine Nepal, 2023)
Dengue fever is a tropical disease which is endemic in tropical/subtropical nations like Nepal. Bilateral optic neuritis with unilateral foveolitis is an unusual dengue-related ophthalmic complication. We here present to you a case of bilateral optic neuritis with right eye foveolitis who initially presented with complaints of sudden diminution of vision in one eye following dengue fever. This report deals with prolonged treatment of rare ocular presentation of dengue infection. Patient had persistent myodesopsia and scotoma in the right eye even after 5 months of treatment with oral steroids. Dengue-related ophthalmic findings although rare, can have significant and long-lasting visual impairment if not treated timely and appropriately.